MODERNISM IN ENGLISH LITERATURE: VIRGINIA WOOLF AND JAMES JOYCE (Ustozlar uchun, 2025)
This paper explores the emergence and development of Modernism in English literature with a particular focus on the works of Virginia Woolf and James Joyce. It analyzes how these writers broke away from traditional narrative forms, introduced psychological depth, experimented with narrative perspective, and redefined the novel as an artistic form. The study highlights the major themes, techniques, and contributions of both authors to the Modernist movement.